3D-printing and the effect on medical costs: a new era?. (2nd January 2016) - Choonara, Yahya E.; du Toit, Lisa C.; Kumar, Pradeep; Kondiah, Pierre P. D.; Pillay, Viness
Abstract : 3D-printing (3DP) is the art and science of printing in a new dimension using 3D printers to transform 3D computer aided designs (CAD) into life-changing products. This includes the design of more effective and patient-friendly pharmaceutical products as well as bio-inspired medical devices. It is poised as the next technology revolution for the pharmaceutical and medical-device industries. After decorous implementation scientists in collaboration with CAD designers have produced innovative medical devices ranging from pharmaceutical tablets to surgical transplants of the human face and skull, spinal implants, prosthetics, human organs and other biomaterials. While 3DP may be cost-efficient, a limitation exists in the availability of 3D printable biomaterials for most applications. In addition, the loss of skilled labor in producing medical devices such as prosthetics and other devices may affect developing economies. This review objectively explores the potential growth and impact of 3DP costs in the medical industry.